Cybertherapy - a modern form of therapy - Marta Makara-Studzińska; Agata Madej (Kazimierz Wielki University, 2017)
Online searching for explanations of failures and crises experienced in daily life leads one to websites offering cybertherapy. The therapy is aimed at people who, for different reasons (e.g. lack of time, shyness), do not wish to have a face-to-face session with the psychotherapist. The main goal of the analysis was the problem of providing the aforementioned psychotherapy. By means of PubMed/MEDLINE, Wiley Online Library, Scopus, Web of Science and Google Scholar science databases, we have searched through Polish and abroad references from 2010-2017 for articles discussing the problem of online psychotherapy. Online psychotherapy possesses many different forms. It can be provided via e-mail, live video session (Skype), chatting or text messages (SMS). The main benefit of e-therapy is its swiftness concentrated on short-term contact. Furthermore, the price is also attractive in comparison to the therapy delivered by traditional means. On the other hand, it has its drawbacks, e.g. lack of emotional contact between the patient and psychotherapist, impersonal relationship and the chance of misunderstandings.